Full Length Research The identification of some biomarkers of coronary arteriosclerosis. Issue 2 (March 2015) - G, G; Shine-Od, Shine-Od; D, D; Aldarmaa, Aldarmaa; T, T; Avirmed, Avirmed; A, A; Bayarmaa, Bayarmaa; E, E; Enebish, Enebish; S, S; Munkhzol, Munkhzol; et al.
No abstract available